2021
DOI: 10.1101/2021.07.10.21259585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on weight and BMI among UK adults: a longitudinal analysis of data from the HEBECO study

Abstract: BackgroundCOVID-19-related restrictions impacted weight and weight-related factors during the initial months of the pandemic. However, longitudinal analyses are scarce.MethodsAn online, longitudinal study was conducted among self-selected UK adults (n=1,818), involving three surveys during 2020 (May-June, August-September, November-December), covering height, weight and sociodemographic, COVID-19-related and behavioural measures. Data were analysed using generalised estimating equations.ResultsSelf-reported av… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…An online longitudinal study among UK adults (n=1818), found that self-reported weight and BMI fluctuated throughout the pandemic. However, in those with an overall increase in weight or BMI, a positive association with monthly intake of HFSS foods and alcohol was found (Dicken et al, 2021). In addition to facing greater risks from Covid-19, those living with obesity were also disproportionately affected by the lockdowns.…”
Section: Impact Of the Pandemic On Weight And Weight-related Behavioursmentioning
confidence: 96%
See 1 more Smart Citation
“…An online longitudinal study among UK adults (n=1818), found that self-reported weight and BMI fluctuated throughout the pandemic. However, in those with an overall increase in weight or BMI, a positive association with monthly intake of HFSS foods and alcohol was found (Dicken et al, 2021). In addition to facing greater risks from Covid-19, those living with obesity were also disproportionately affected by the lockdowns.…”
Section: Impact Of the Pandemic On Weight And Weight-related Behavioursmentioning
confidence: 96%
“…A review exploring the pandemic's influence on lifestyle behaviours found that intake of snack foods, often high in fat, sugar and salt (HFSS), increased in the first lockdown, often as a coping mechanism while self-isolating (Bennett et al, 2021;Kass et al, 2021). Physical activity levels also declined, sedentary behaviours increased (Ammar et al, 2020;Kass et al, 2021), and many individuals reported weight gain (Bennett et al, 2021;Dicken et al, 2021;Kass et al, 2021). One international online survey of 1047 respondents in Europe, Asia and Africa found that sitting time increased from 5 to 8 hours daily, while all levels of physical activity decreased (Ammar et al, 2020).…”
Section: Impact Of the Pandemic On Weight And Weight-related Behavioursmentioning
confidence: 99%
“…Given the evidence for links between PA and other health behaviours, reductions in PA during the COVID-19 pandemic may have had negative impacts on other health behaviours. However, early evidence suggests there has been extensive individual variation in changes in health behaviours during the pandemic, with studies reporting improvements in diet 33 40 , alcohol consumption 41 43 , and sleep for some individuals 35 , 44 , 45 , despite evidence of population level decreases in PA, increases in sedentary time 27 , 46 , 47 and alcohol consumption 41 , 48 , 49 , and worse dietary choices 38 . The relationship between PA and these health behaviours is likely confounded by other major changes to people’s lives such as having to strictly isolate, family or financial adversity, children not being at school, or psychological distress in the wake of social restrictions 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence for links between PA and other health behaviours, reductions in PA during the COVID-19 pandemic may have had negative impacts on other health behaviours. However, early evidence suggests that there has been extensive individual variation in changes in health behaviours during the pandemic, with studies reporting improvements in diet [33][34][35][36][37][38][39][40], alcohol consumption [41][42][43], and sleep for some individuals [35,44,45], despite evidence of population level decreases in PA, increases in sedentary time [27,46,47], alcohol consumption [41,48,49], and worse dietary choices [38]. The relationship between PA and these health behaviours is likely confounded by other major changes to people's lives such as having to strictly isolate, family or financial adversity, children not being at school, or psychological distress in the wake of social restrictions [50].…”
Section: Introductionmentioning
confidence: 99%